Effect of service quality and motivation on the consumption behavior of students in the academic services - Kuswanto Kuswanto; Irzal Anderson (Institute of Advanced Engineering and Science, 2021)
This study aimed to determine the effect of service quality and motivation to the consumption behavior of students in utilizing academic services. This research involved 87 students of Economic Education Study Program in University of Jambi, Indonesia. The data were analyzed using structural equation modeling with partial least squares technique (SEM-PLS). Student consumption behavior is an illustration of the level of satisfaction in utilizing academic services provided by universities. Satisfaction with academic services is a measure of the success of higher education performance in providing education. A good indicator of consumer behavior variables, namely making the University of Jambi academic services the best choice and choosing them as institutions of higher education to meet learning needs on an ongoing basis. The quality of academic services is shown by indicators of the reliability of officers in providing academic services, accuracy in the delivery of information, responsiveness in responding to complaints and student requests and harmonization of service relationships between officers and students. While consumption motivation is indicated by an indicator of trust in the services consumed it will facilitate the completion of academic affairs and the existence of attractive offers from higher education institutions. The quality of academic services has a significant effect on consumer behavior of students. Moreover, the consumption motivation variable is proven to be a significant mediator on the effect of service quality on student’s consumption behavior.